Phonological Language Errors in the TikTok Comments Column of @diansoediro and Their Relevance to Indonesian Language Learning - Amelia Anastasya Lanti; Ulfa Zakaria; Nuramila (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to analyze and describe phonological errors, including phoneme changes, phoneme omissions, and phoneme additions, in the comments column of the TikTok social media account @diansoediro, and to determine their relevance to Indonesian language learning materials in schools. This study uses a qualitative descriptive approach with a phenomenological approach. The research data consists of words found in the comments column of the TikTok account @diansoediro from January to December 2024. Data collection techniques were carried out using listening, note-taking, and documentation techniques. The data analysis technique includes three stages: data reduction, data presentation, conclusion drawing, and verification. The results of this study indicate that 39 phonological errors were found, consisting of 6 phoneme changes (adaptation, contraction, and metathesis); 6 phoneme omissions (apheresis, syncope, and apocope); and four additional phoneme data in the form of epenthesis and paragogue. Phonological errors are relevant to Indonesian language learning. Phonological errors are influenced by daily habits, the tendency to write spontaneously, and the informal nature of digital communication. These findings have significant relevance to Indonesian language learning in schools, particularly the writing element in Phase D Learning Outcomes. Therefore, these language error data can be used as a contextual resource to improve students' accuracy and language skills.